Vasogenic Cerebral Edema following CT Myelogram with Nonionic Omnipaque 300 - Sara Khodor; Scott Blumenthal (Case Reports in Neurological Medicine)
Computed Tomography (CT) with myelogram is a relatively safe procedure. It requires the use of nonionic contrast agents which, unlike ionic contrast agents, have been associated with low complication rates. We report a case of a 69-year-old female who developed diffuse bilateral cerebral edema following a lumber myelogram with the use of intrathecal nonionic contrast agent Omnipaque (Iohexol) 300. We were able to find one other reported case of cerebral edema following the use of intrathecal nonionic contrast agent in the literature.